Interaction between childhood vocal fold nodules and allergic diseases. (November 2020) - Ercan, Nazli; Bostanci, Ilknur; Kaygusuz, Umut; Ceylan, Kamercan
Abstract: Objectives: Vocal fold nodules (VFNs) are benign lesions at the junction of the anterior and middle third of the vocal folds. Although VFNs are often a result of vocal cord trauma due to vocal abuse, childhood allergic diseases, and medications may be a cause. We aimed to investigate the association of detected VFNs with allergic diseases in childhood patients with vocal abuse. Methods: This is a prospective, cross-sectional, case-control study. Caucasian children in ages 3–12, who speak loud, vocal abuse confirmed with Turkish Children's voice handicap index-10 (TR-CVHI-10) above 9 were enrolled to the study. 33 children with VFN were included as the study group and age-matched 26 healthy children without VFN were included as the control group. Children questioned and tested for allergic diseases with Allergometric tests. Results: Asthma was detected in 42.4% of the study group and absent in the control group. The history of inhaler or nasal steroid use was positive in 30.3% of the study group and 7.7% of the control group (p = 0.032). Dysphonia and the presence of allergic diseases were determined as independent risk factors for the study group (p = 0.001; 0.021, respectively). The median values of blood lymphocyte counts were significantly different among study and control groups (2900 μl vs 2335 μl, respectively; p = 0.04). Conclusion: Investigating allergic diseases, especially asthma, for success in the treatment of pediatric patients with VFNs is of utmost importance.